2014
DOI: 10.1111/sms.12243
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in neuromuscular function of the plantar flexors following caffeine ingestion

Abstract: The aim of this study was to compare the neuromuscular function of the plantar flexors following caffeine or placebo administration. Thirteen subjects (25 ± 3 years) ingested caffeine or placebo in a randomized, controlled, counterbalanced, double-blind crossover design. Neuromuscular tests were performed before and 1 h after caffeine or placebo intake. During neuromuscular testing, rate of torque development, isometric maximum voluntary torque, and neural drive to the muscles were measured. Triceps surae musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 43 publications
(67 reference statements)
5
28
1
1
Order By: Relevance
“…The H-reflex during MVC (H sup ) was elicited 2 s after torque onset during the plateau of the torque-time curve at H max intensity to record the small M-wave preceding H sup (M H sup ) and H sup (Duclay et al 2008;Behrens et al 2014). It is possible that H sup did not represent the maximal H-reflex during MVC.…”
Section: Electrical Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The H-reflex during MVC (H sup ) was elicited 2 s after torque onset during the plateau of the torque-time curve at H max intensity to record the small M-wave preceding H sup (M H sup ) and H sup (Duclay et al 2008;Behrens et al 2014). It is possible that H sup did not represent the maximal H-reflex during MVC.…”
Section: Electrical Stimulationmentioning
confidence: 99%
“…The individual positioning for each participant was equal before and after 8 weeks of training. The subjects were seated with their knees straight and their foot firmly attached to the adapter of the dynamometer (Ekblom 2010;Behrens et al 2014). Velcro straps and a snowboard binding were used to fasten the subjects' feet on the metal plate of the dynamometer.…”
Section: Emg and Torque Recordingsmentioning
confidence: 99%
“…(2006) and by Behrens et al. (2015a, b), but contrary to other studies where an enhancement of the peak‐to‐peak maximal normalized H‐reflex (Kalmar & Cafarelli, 1999) and of the normalized slope of the H‐reflex recruitment curve (Walton et al., 2003) were observed. Walton et al.…”
Section: Discussionmentioning
confidence: 61%
“…Effects of caffeine on the excitability of spinal motoneurons are likely but far from unequivocal. Some authors have shown a positive effect in a non‐fatigued state (Kalmar & Cafarelli, 1999; Walton, Kalmar, & Cafarelli, 2002, 2003) and during fatigue (Kalmar et al., 2006), whereas others did not observe a significant effect in a non‐fatigued state (Behrens et al., 2015a, b; Kalmar et al., 2006). Some studies have attributed the ergogenic effects of caffeine to a decreased inhibition at the cortical or spinal level (Cerqueira, de Mendonça, Minez, Dias, & de Carvalho, 2006; de Carvalho, Marcelino, & de Mendonça, 2010) and an increased corticospinal excitability (Kalmar & Cafarelli, 2004, 2006), both of which may contribute to enhancement of descending neural drive.…”
Section: Introductionmentioning
confidence: 99%
“…The axis of the dynamometer was aligned with the anatomical flexion‐extension axis. The athletes were fixed to the dynamometer as described previously (Behrens et al., , , ). The isometric maximum voluntary torque (iMVT) was measured during the following isometric MVC tasks: eversion, plantar flexion, dorsal flexion, knee flexion, and knee extension.…”
Section: Methodsmentioning
confidence: 99%